2009
DOI: 10.1155/2009/859271
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Contemporary Developments in the Management of Patients with Gastroesophageal Reflux Disease Undergoing an Initial Gastroscopy

Abstract: Among patients presenting with GERD-like symptoms, the prevalence of Barrett's esophagus may increase markedly if the Montreal definition is adopted. In addition, growing awareness of EE may lead to an increase in the prevalence of this diagnosis. Prospective studies of the management implications of these findings are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
3
0
3
Order By: Relevance
“…For example, the rate of esophageal adenocarcinogenesis discovered in this screening population was consistent with that reported for the general GERD population by other authors. 42-47 Also, previously established risk factors for esophageal adenocarcinogenesis, such as age, sex, ethnicity, and presence of hiatal hernia, were confirmed and reproduced in this study. Although this study is the first, to our knowledge, to examine the relationship among the severity of GERD symptoms, PPI use, and esophageal adenocarcinogenesis, others have demonstrated an increased risk of esophageal adenocarcinogenesis for patients taking PPIs.…”
Section: Commentsupporting
confidence: 82%
“…For example, the rate of esophageal adenocarcinogenesis discovered in this screening population was consistent with that reported for the general GERD population by other authors. 42-47 Also, previously established risk factors for esophageal adenocarcinogenesis, such as age, sex, ethnicity, and presence of hiatal hernia, were confirmed and reproduced in this study. Although this study is the first, to our knowledge, to examine the relationship among the severity of GERD symptoms, PPI use, and esophageal adenocarcinogenesis, others have demonstrated an increased risk of esophageal adenocarcinogenesis for patients taking PPIs.…”
Section: Commentsupporting
confidence: 82%
“…A retrospective study of 353 patients with reflux symptoms reported that 7.7% of those biopsied at endoscopy had EoE. 22 A retrospective review of 161 patients having endoscopy for noncardiac chest pain reported that 6% had EoE. 23 An insidious onset of symptoms and self-taught coping strategies such as food avoidance (eg, difficult to swallow textures such as bread and meat) and drinking large volumes of water with meals, can delay patients recognition and reporting of symptoms.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A retrospective study of 353 patients with reflux symptoms reported that 7.7% of those biopsied at endoscopy had EoE. 22 A retrospective review of 161 patients having endoscopy for non-cardiac chest pain reported that 6% had EoE. 23 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…Sofern eine Dysphagie oder eine Bolusobstruktion vorlagen liegt die Inzidenz sogar bei 23-50 %, beim Vorliegen therapierefraktärer GERD-Symptome oder bei nicht kardialen Thoraxschmerzen bei 0,9-8 % bzw. 6 % [24], [25], [26], [27]. Eine EoE kann in allen Altersklassen auftreten.…”
Section: Kommentarunclassified